Perancangan Hotel Bisnis Di Balikpapan Dengan Pendekatan Arsitektur Tropis - Sulistria; Gunawan; Rusyd; Zuraida (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2023)
The majority of hotels in Balikpapan use a modern look that does not accommodate tropical climate conditions. In addition, hotels in Balikpapan are also somewhat inconsistent with local architecture, so the buildings do not have a character that reflects local culture. This is one of the main reasons for designing hotels in Balikpapan with a tropical architectural approach. The character of this Tropical Architecture is the approach that will be applied to this design to anticipate tropical climate conditions which have quite high temperatures and humidity. The design approach that will be applied to the building is the determination of spatial orientation, shading, cross ventilation (air circulation), lighting and the use of traditional Dayak motifs. The method used in this design is the rational method. It is hoped that the Hotel Design in Balikpapan with a Tropical Architectural Approach can become a design that can accommodate the tropical climate, support the needs of people who are on business trips and become buildings that have local cultural characteristics in Balikpapan.